2016
DOI: 10.21077/ijf.2016.63.4.60271-20
|View full text |Cite
|
Sign up to set email alerts
|

Food and feeding habits of the greenback grey mullet Liza subviridis (Valenciennes, 1836) from Parangipettai waters, south-east coast of India

Abstract: The feeding ecology and prey preference of greenback grey mullet Liza subviridis (Valenciennes, 1836) were investigated in Parangipettai waters (11°29′25.55″N; 79°45′38.62″E) from May 2011 to April 2012. A total of 328 male and 360 female specimens of L. subviridis were analysed. Detritus and sand particles formed the major food item of L. subviridis in both sexes besides, diatoms, dinoflagellates, algae, zooplankton, foraminiferans, polychaetes and larval forms were also noticed and ranked respectively based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Also, Mohamed and Abood [26] found that the highest values of the vacuity index of P. klunzengeri and P. subviridis in the Shatt Al-Arab River were in winter, and the overall values of the vacuity index for both species were 17.2 and 20.7%, respectively. The value of the vacuity index of P. subviridis varied from 7.2% (November) to 19.3% (August) in males, while in females ranged from 7.1% (March) to 19.2% (August) in the Parangipettai waters, India [22]. Nikolsky [45] deduced that water temperature plays a substantial role in food intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Mohamed and Abood [26] found that the highest values of the vacuity index of P. klunzengeri and P. subviridis in the Shatt Al-Arab River were in winter, and the overall values of the vacuity index for both species were 17.2 and 20.7%, respectively. The value of the vacuity index of P. subviridis varied from 7.2% (November) to 19.3% (August) in males, while in females ranged from 7.1% (March) to 19.2% (August) in the Parangipettai waters, India [22]. Nikolsky [45] deduced that water temperature plays a substantial role in food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Jabir and Al-Hisnawi [14] found that P. subviridis in Khor Al-Zubair, Iraq fed on detritus (35.1%), diatoms (20.0%), crustacean (6.3%) and high plants (6.2%) and Mohamed et al [15] stated that the species fed mainly on detritus (19.1%), diatoms (16.7%), high plants (12.7%) and algae (12.5%) in the Iraqi marine waters. Ashiq Ur Rahman et al [22] found that P. subviridis in the Parangipettai waters, India consumed detritus, diatoms, dinoflagellates, algae, zooplankton, polychaetes, foraminiferans, larval forms and miscellaneous items. Similar results were obtained for the other species of the mullet, Ellochelon vaigiensis in the Mekong Delta, Vietnam, where detritus was the essential food in the diet composition of the species and did not vary with sex, body size, season, and sampling site [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullets are distributed in temperate and tropical regions and occur in freshwater and marine habitats (Nelson et al., 2016). They are significant contributors to the energy flow of food webs in estuarine ecosystems (Rahman et al., 2016); gray mullets ( Mugil cephalus ) for example, are bottom‐dwelling species that consume decomposed organic matter, algae, and diatoms (El‐Marakby et al., 2006; Mondal et al., 2015). In 2016, the global yield of mullets totaled 763,291 tons, of which 76.8% were from capture fisheries (585,959 tons) and about 23.2% from aquaculture (177,332 tons) (FAO, 2018).…”
Section: Introductionmentioning
confidence: 99%